Association of Serum Magnesium with Sputum Smear Conversion at the end of 2nd month among Smear Positive Pulmonary Tuberculosis Patients (Chest & Heart Journal, 2021)
Background: The progress of an infectious condition is partly affected by the overall nutrition of the host. Many of the essential trace elements like zinc, copper, magnesium influence the function of the immune system. Magnesium levels also influence tuberculosis. Tuberculosis and malnutrition is well recognized to go hand in hand as one can lead to the other.Methods: This prospective observational study was conducted at the Department of Respiratory Medicine in National Institute of Diseases of the Chest and Hospital from July 2018 to June 2020. A total of 85 new smear positive pulmonary tuberculosis cases were enrolled in this study. Serum Magnesium was measured by the colorimetric method using Xylidyl Blue-I. Statistical analyses of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-23).Results: In this study 74(87.1%) patients had sputum smear conversion and 11(12.9%) had delayed sputum smear conversion at the end of intensive phase of treatment. Mean initial serum magnesium was 1.95±0.26 mg/dl and mean serum magnesium at the end of 2nd month was 2.07±0.24 mg/dl. Significant association was found in sputum smear conversion with smoking, initial serum magnesium level and serum magnesium level at the end of 2nd month. There was no significant association of sputum smear conversion with diabetes mellitus and BMI. In multivariate logistic regression analysis, initial low serum magnesium level and smoking were found to be independent predictors for sputum smear non-conversion at the end of 2nd month but low serum magnesium at the end of 2nd month was not found to be independent predictor for sputum smear non-conversion.Conclusion: Hypomagnesaemia at the initiation of anti-tubercular therapy was significantly associated with sputum smear non-conversion at the end of intensive phase of treatment.Chest Heart J. 2020; 44(2) : 82-88